Interaction of SH‐SY5Y Cells with Nanogratings During Neuronal Differentiation: Comparison with Primary Neurons. Issue 4 (1st October 2013) - Tonazzini, Ilaria; Cecchini, Alessandra; Elgersma, Ype; Cecchini, Marco
<x xml:space="preserve">Abstract</x> Controlling neuronal cell adhesion, migration, and axonal outgrowth via contact interactions with biomaterials is a critical element for tissue engineering applications and for developing artificial neuronal interfaces. One promising approach relies on the exploitation of nanostructured surfaces. Here, the human neuroblastoma cell line SH‐SY5Y is interfaced with plastic nanogratings (NGs; anisotropic topographies composed by alternating lines of grooves and ridges with sub‐micrometer lateral dimension). The SH‐SY5Y cells' (SHs) contact guidance is investigated under proliferating conditions and upon differentiation after treatment with retinoic acid (RA) and brain‐derived neurotrophin factor (BDNF), and compared with mouse primary hippocampal neurons (HNs). Quantitative readouts are obtained by measuring changes in tubulin cytoskeleton organization and cell morphology induced by mechanotransduction. Results demonstrate that SHs effectively retrieve substrate topographical signals, in particular during differentiation. Remarkably, RA/BDNF improves SH responsiveness to NG directional cues, and significantly enhances the alignment to the NG lines. HNs behave similarly, showing a marked change in network organization if cultured on NGs. These results might help the rational engineering of neuro‐regenerative scaffolds to improve peripheral nerve wound healing, as well as to investigate the basic mechanisms of neuronal wiring.